2017
DOI: 10.14720/aas.2017.109.3.01
|View full text |Cite
|
Sign up to set email alerts
|

Maximizing land productivity by diversified cropping systems with different nitrogen fertilizer types

Abstract: Six field experiments were conducted in Giza Agricultural Research Station, Egypt during 2010, 2011 and 2012 growing seasons to study the effect of two types of N fertilizers (urea and urea form as slow-release (UF)) on intercropping cowpea with sunflower and intercropping wheat with pea. A split plot design with three replications was used. The results indicated that insignificant effect of cropping systems was found for sunflower and significant effect was found for cowpea yield. Significant effect of N fert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 13 publications
(10 reference statements)
2
3
0
1
Order By: Relevance
“…These increases due to mixing slowrelease nitrogen fertilizer may be attributed to minimizing the loss of nitrogen by leaching, retarded nitrification besides saving a suitable amount of nitrogen as plant need during the different stage life which increased growth and root yield was reflected on NUE. Similar finding was reported by Abdel-Wahab and El Manzlawy (2016), Zohry et al (2017). Dou and Alva (1998) found that the total N uptake by seedlings was higher for the controlled release fertilizers than conventional urea.…”
Section: Effect Of Slow-release N Fertilizer Ratessupporting
confidence: 88%
See 3 more Smart Citations
“…These increases due to mixing slowrelease nitrogen fertilizer may be attributed to minimizing the loss of nitrogen by leaching, retarded nitrification besides saving a suitable amount of nitrogen as plant need during the different stage life which increased growth and root yield was reflected on NUE. Similar finding was reported by Abdel-Wahab and El Manzlawy (2016), Zohry et al (2017). Dou and Alva (1998) found that the total N uptake by seedlings was higher for the controlled release fertilizers than conventional urea.…”
Section: Effect Of Slow-release N Fertilizer Ratessupporting
confidence: 88%
“…These results are in harmony with those obtained by Abdel-Wahab and El Manzlawy (2016) who found that decreasing wheat density from 6 to 4 rows intercropping with faba bean with increasing N slowrelease fertilizer to 238 kg/ha gradually increased LER. These results confirmed by Zohry et al (2017).…”
Section: Interaction Effect Between Onion Plant Density and Slow-relesupporting
confidence: 79%
See 2 more Smart Citations
“…Por otro lado, el manejo de los fertilizantes es una parte indispensable de la agricultura y una de las inversiones más importantes en todo cultivo, esto se debe en parte al aumento de los costos, particularmente del fertilizante nitrogenado (Pibars et al, 2015;Zohry et al, 2017), ya que el nitrógeno es uno de los nutrientes minerales más importantes en la producción de cultivos (Zohry et al, 2017) y el que posee una mayor demanda en la agricultura (Figueiredo-Lobo & Grassi-Filho, 2009). El nitrógeno es fácilmente absorbido por las plantas en forma de nitrato (NO3), urea (CO(NH2)2) y amonio (NH 4+ ) (Ozturk et al, 2017).…”
Section: Introductionunclassified